Penerapan Model Pembelajaran Peer Teaching Dalam Mengembangkan Keterampilan Kolaborasi Peserta Didik Pada Pembelajaran Pendidikan Agama Islam - Mahardika, Mutiara; Botifar, Maria (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
Islamic Religious Education (PAI) learning requires students to be active and collaborative, yet learning practices in schools are often teacher-centered, resulting in underdevelopment of collaborative skills. This situation indicates a gap between the needs of 21st-century learning and the methods used. This study examines the implementation of the peer teaching model as an effort to develop students' collaborative skills through a case study at SMP IT Al-Husna Lebong. The research objective was to describe the planning, implementation process, and evaluation of the peer teaching model in Islamic Religious Education (PAI) learning. This qualitative research used observation, interviews, and documentation techniques, with data analysis using the Miles & Huberman model. The results showed that peer teaching was planned through a lesson plan (RPP) that included learning syntax including group formation, peer guru preparation, guru delivery, teacher clarification, and reflection. During the implementation phase, students demonstrated increased engagement, collaboration, communication, and group responsibility. Evaluation, conducted through observations of collaborative attitudes and learning outcome tests, demonstrated that peer teaching effectively improved the quality of interactions and understanding of Islamic Religious Education (PAI) material. This model has proven to be superior in creating active, participatory, and more meaningful learning. The study concluded that peer teaching is a relevant and effective model for developing students' collaboration skills in Islamic Religious Education (PAI) learning. Recommendations are directed at teachers to expand the use of this model and improve training for peer gurus to strengthen the quality of learning.